Defect-engineered magnetic bismuth nanomedicine for dual-modal imaging and synergistic lung tumor therapy - Pengpeng Jia; Jie Tu; Hongyu Shen; Yuqin Jiang; Qiupeng Zhang; Weixian Xue; Meitong Liu; Jianbo Liu; Yuqing Miao; Ruizhuo Ouyang; Shuang Zhou (Materials Today Bio)
Bismuth sulfide (Bi2S3) nanomaterials are recognized for their potential in tumor therapy due to their narrow bandgap and low toxicity. However, limited photothermal conversion efficiency (PCE) and low carrier density restrict their broader application in photothermal cancer treatment. To address these challenges, we designed defect-engineered, magnetic-targeting Bi2S3-based photothermal nanoparticles, Fe3O4@Au@Bi2S3 nanorugbys (Fe3O4@Au@Bi2S3 NRs). These nanoparticles were developed using a layer-by-layer encapsulation strategy with sulfur vacancies (Vs) and Bi antisite defects (Bi replacing S, Bis), enhancing electron trapping and recombination to boost the near-infrared (NIR) response. The PCE of Fe3O4@Au@Bi2S3 NRs reached 44.34 %, which significantly improved their efficacy in photothermal treatment for lung tumors. Moreover, the polyvinylpyrrolidone (PVP) coating on the nanoparticles enabled efficient loading and pH-responsive release of doxorubicin hydrochloride (DOX), facilitating synergistic chemo-photothermal therapy. When exposed to an external magnetic field, the nanoparticles demonstrated strong magnetic targeting and enhanced computed tomography (CT) imaging capabilities, improving tumor treatment accuracy. Both in vitro and in vivo studies showed that this combined therapy effectively induced cancer cell apoptosis and inhibited tumor proliferation, showcasing outstanding anti-tumor performance. This study provides a promising strategy for enhancing chemo-photothermal therapy through defect-engineered, magnetic-targeted Fe3O4@Au@Bi2S3 nanoparticles, holding significant potential for clinical applications in tumor therapy.